The WNBA and athletic performance based on sexual orientation - Willis, J.; Bek Awrang Zeb, T.; Haydel, J.; Wu, J.; Yim, S.; Satchwell, M.; Saraf, Y.; Hensley, M. (PsyArXiv, 2022)
The success of Title IX and the LGBTQ rights movement is embodied in the sexual orientation diversity and inclusiveness of the WNBA. This makes the WNBA one of the only sports where a comparison of athletic performance based on sexual orientation is possible. Sex differences in athletic performance emerge during puberty, due in part to increases in circulating testosterone in men. Research has also found that lesbians and bisexual women have more testosterone than straight women. Thus, it is possible that there are differences in women`s athletic performance based on sexual orientation. In this study, we used publicly available information to determine the sexual orientation of current WNBA players and compared performance statistics based on sexuality. Results showed that straight guards and forwards weighed more than lesbians, whereas the reverse was true for centers. Lesbian guards are more accurate shooters with a significantly higher field goal percentage than straight guards, and lesbian forwards recorded marginally more steals and assists than straight forwards. Straight females committed more personal fouls than lesbians, especially if they had a female coach in college (regardless of the sex of their WNBA coach). Aside from these findings, overall performance was similar regardless of athletes` sexual orientation. We argue that no athlete should be discounted based on sexual orientation, whether straight athletes in women`s sports or gay athletes (like Michael Sam) in men`s sports.